Decline of cardiomyocyte contractile performance and bioenergetic function in socially stressed male rats. Issue 11 (November 2022) - Barbetti, Margherita; Vilella, Rocchina; Dallabona, Cristina; Gerra, Maria Carla; Bocchi, Leonardo; Ielpo, Donald; Andolina, Diego; Sgoifo, Andrea; Savi, Monia; Carnevali, Luca
Abstract: Chronic social stress has been epidemiologically linked to increased risk for cardiovascular disease, yet the underlying pathophysiological mechanisms are still largely elusive. Mitochondrial (dys)function represents a potential intersection point between social stress exposure and (mal)adaptive cardiac responses. In this study, we used a rodent model of social stress to study the extent to which alterations in the cellular mechanical properties of the heart were associated with changes in indexes of mitochondrial function. Male adult rats were exposed to repeated episodes of social defeat stress or left undisturbed (controls). ECG signals were recorded during and after social defeat stress. Twenty-four hours after the last social defeat, cardiomyocytes were isolated for analyses of mechanical properties and intracellular Ca 2+ dynamics, mitochondrial respiration, and ATP content. Results indicated that social defeat stress induced potent cardiac sympathetic activation that lasted well beyond stress exposure. Moreover, cardiomyocytes of stressed rats showed poor contractile performance (e.g., slower contraction and relaxation rates) and intracellular Ca 2+ derangement (e.g., slower Ca 2+ clearing), which were associated with indexes of reduced reserve respiratory capacity and decreased ATP production. In conclusion, this study suggests that repeated social stress provokes impaired cardiomyocyte contractile performance and signs of altered mitochondrial bioenergetics in the rat heart. Future studies are needed to clarify the causal link between cardiac and mitochondrial functional remodeling under conditions of chronic social stress. Abstract : Social stress; Cardiomyocyte; Mitochondria; ATP; Intracellular calcium dynamics; Heart rate.